2010
DOI: 10.3233/jad-2010-1314
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 Receptor Stimulation Reduces Amyloid-β Peptide Accumulation and Cytotoxicity in Cellular and Animal Models of Alzheimer's Disease

Abstract: Type 2 (T2) diabetes mellitus (DM) has been associated with an increased incidence of neurodegenerative disorders, including Alzheimer's disease (AD). Several pathological features are shared between diabetes and AD, including dysfunctional insulin signaling and a dysregulation of glucose metabolism. It has therefore been suggested that not only may the two conditions share specific molecular mechanisms but also that agents with proven efficacy in one may be useful against the other. Hence, the present study c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
225
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(245 citation statements)
references
References 72 publications
19
225
0
1
Order By: Relevance
“…IR inhibition can thus greatly elevate extracellular Aβ oligomers. This downregulation in the internalization of Aβ may explain previously reported reductions in Aβ pathology seen in insulin-resistant neurons, animal models of AD, and diabetic humans after treatment with insulin plus antidiabetic agents (119) or the IR-sensitizing agents metformin (120) and glucagon-like peptide 1 (GLP-1) mimetics (121)(122)(123)(124)(125).…”
Section: Figurementioning
confidence: 69%
See 1 more Smart Citation
“…IR inhibition can thus greatly elevate extracellular Aβ oligomers. This downregulation in the internalization of Aβ may explain previously reported reductions in Aβ pathology seen in insulin-resistant neurons, animal models of AD, and diabetic humans after treatment with insulin plus antidiabetic agents (119) or the IR-sensitizing agents metformin (120) and glucagon-like peptide 1 (GLP-1) mimetics (121)(122)(123)(124)(125).…”
Section: Figurementioning
confidence: 69%
“…Metformin (120, 165) and 2 GLP-1 mimetics (121, 124, 125, 165, 166) are antidiabetic agents approved by the FDA without restriction; all have excellent safety profiles, readily cross the bloodbrain barrier, and raise insulin-induced IR and IRS-1 activation. These agents are all neuroprotectants (120,167,168) that reduce extracellular Aβ levels in cultures of insulin-resistant neurons (120,122) and in AD mouse models (122,124). In such mice, the GLP-1 mimetic liraglutide decreases oligomeric Aβ, neuritic plaque load, and microglial activation; elevates neurogenesis; restores LTP; and improves object recognition and spatial memory (124,169).…”
Section: Figurementioning
confidence: 99%
“…ICV‐infused (Val 8 )GLP‐1 or GIP reversed impairment of LTP induced by Aβ32, 33, 70. ICV‐infused liraglutide and peripherally‐administered exendin‐4 also enhanced LTP in an AD model31, and in a diabetes‐related AD model80. One study showed that peripherally‐administered D‐Ala 2 GIP facilitated synaptic plasticity in mice at an advanced state of AD81.…”
Section: Type 2 Diabetes Mellitus Dementia and Incretin‐based Therapiesmentioning
confidence: 99%
“…Neuronal cell line studies showed that exendin‐4 reduced the levels of Aβ80, other neuronal cell line studies found that exendin‐4 reduced levels of APP, but had no impact on Aβ levels42, 80. In rodent models of AD, peripherally‐administered geniposide and D‐Ala 2 GIP reduced levels of Aβ plaque load81, 83, 84, 85.…”
Section: Type 2 Diabetes Mellitus Dementia and Incretin‐based Therapiesmentioning
confidence: 99%
“…[35][36][37] Although there is a low risk of hypoglycaemia, the effects on weight loss and increasing satiety effects may not be beneficial in this cohort of patients where appetite may already be suppressed. Their limited use in moderate to severe renal impairment also restricts their benefit.…”
Section: Non-insulinsmentioning
confidence: 99%